2013
DOI: 10.1016/j.yexcr.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3 regulates expression of nuclear factor-erythroid-2 related transcription factor-1 (Nrf1) and inhibits pro-survival function of Nrf1

Abstract: Nuclear factor E2-related factor-1 (Nrf1) is a basic leucine zipper transcription factor that is known to regulate antioxidant and cytoprotective gene expression. It was recently shown that Nrf1 is regulated by SCF-Fbw7 ubiquitin ligase. However our knowledge of upstream signals that targets Nrf1 for degradation by the UPS is not known. We report here that Nrf1 expression is negatively regulated by glycogen synthase kinase 3 (GSK3) in Fbw7-dependent manner. We show that GSK3 interacts with Nrf1 and phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…5A, upper and lower panels ); this was, however, accompanied by decreased expression level of the ∼120kDa mNrf1 glycoprotein ( middle panel ). Taken together with other MG132‐based experimental evidence showing that the turnover of Nrf1/TCF11 occurs via Hrd1‐, SCF β‐TrCP ‐ and/or SCF FBW7 ‐directed ubiquitin‐mediated protein degradation pathways [22,57–59], it is therefore postulated that O ‐GlcNAcylation of mNrf1 by OGT enables destabilization of the CNC‐bZIP protein, possibly via the ubiquitin‐proteasomal degradation pathway, albeit detailed mechanistic studies are required.…”
Section: Resultsmentioning
confidence: 99%
“…5A, upper and lower panels ); this was, however, accompanied by decreased expression level of the ∼120kDa mNrf1 glycoprotein ( middle panel ). Taken together with other MG132‐based experimental evidence showing that the turnover of Nrf1/TCF11 occurs via Hrd1‐, SCF β‐TrCP ‐ and/or SCF FBW7 ‐directed ubiquitin‐mediated protein degradation pathways [22,57–59], it is therefore postulated that O ‐GlcNAcylation of mNrf1 by OGT enables destabilization of the CNC‐bZIP protein, possibly via the ubiquitin‐proteasomal degradation pathway, albeit detailed mechanistic studies are required.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Nrf1 is regulated by phosphorylation. Glycogen Synthase Kinase 3 (GSK3) was previously demonstrated to negatively regulate Nrf1a stability [69]. Phosphorylation of Nrf1a facilitated by GSK3 was shown to recruit Fbw7, the Fbox containing ubiquitin ligase, for proteasomal degradation of Nrf1a.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the dys-regulation NFE2L1 protein might lead tumor [11]. Another study also suggested that NFE2L1 expression is related to the cell survival under stress condition [12]. A recent study found that USP15 protein regulates the TGF-β pathway and USP15 has an important International Journal of Bioscience, Biochemistry and Bioinformatics role in glioblastoma cancer [13].…”
Section: Resultsmentioning
confidence: 99%